Phase 1–3 of the cross‐cultural development of an EORTC questionnaire for the assessment of sexual health in cancer patients: the EORTC SHQ‐22 - Anne Sophie Oberguggenberger; Eva Nagele; Elisabeth C. Inwald; Krzysztof Tomaszewski; Anne Lanceley; Andy Nordin; Carien L. Creutzberg; Karin Kuljanic; Dimitrios Kardamakis; Claudia Schmalz; Juan Arraras; Anna Costantini; et al. (Cancer Medicine, 2018)
Abstract To develop and pretest an European Organization for the Research and Treatment of Cancer Sexual Health Questionnaire (EORTC SHQ‐22) for the assessment of physical, psychological, and social aspects of sexual health (SH) in male and female cancer patients and survivors. Questionnaire construction started with creating a list of relevant SH issues based on a comprehensive literature review. Issues were subsequently evaluated for relevance and prioritization by 78 healthcare professionals (HCP) and 107 patients from 12 countries during in‐depth interviews (phase 1). Extracted issues were operationalized into items (phase 2). Phase 3 focused on pretesting the preliminary questionnaire in a cross‐cultural patient sample (n = 171) using debriefing interviews. Psychometric properties were preliminary determined using a principal component analysis and Cronbach's alpha. We derived 53 relevant SH issues from the literature. Based on HCP and patient interviews, 22 of these 53 issues were selected and operationalized into items. Testing the preliminary 22‐item short questionnaire resulted in a change of wording in five items and two communication‐related items; no items were removed. Preliminary psychometric analysis revealed a two‐factor solution and 11 single items; both scales showed good reliability indicated by a Cronbach's alpha of 0.87 (sexual satisfaction) and 0.82 (sexual pain). Cross‐cultural pretesting of the preliminary EORTC SH questionnaire has indicated excellent applicability, patient acceptance, and comprehensiveness as well as good psychometric properties. The final development phase, that is psychometric validation (phase four) including large‐scale, cross‐cultural field testing of the EORTC SHQ‐22, has commenced.